2019
DOI: 10.1007/s00432-019-03036-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating lymphocytes and CD8+ T cells predict survival of triple-negative breast cancer

Abstract: Purpose Tumor inflammatory response was evaluated as a prognostic feature in triple-negative breast cancer (TNBC) and compared with the clinical prognosticators of breast cancer and selected biomarkers of cancer cell proliferation. Methods TNBC patients (n = 179) with complete clinical data and up to 18-year follow-up were obtained from Auria biobank,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
4
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 56 publications
9
66
4
4
Order By: Relevance
“…Studies have proved that TIL levels have a strong prognostic value, which can improve the distant recurrence-free survival, disease-free, and overall survival estimates for TNBC patients treated with adjuvant/neoadjuvant chemotherapy (22,23). Increased TIL levels have been observed to be positively correlated with prolonged survival and increased pathological complete response rates (24)(25)(26). Because of the uneven distribution of TILs within the tumor, TIL levels obtained by biopsy in a specific part of the tumor may not reflect the entire tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proved that TIL levels have a strong prognostic value, which can improve the distant recurrence-free survival, disease-free, and overall survival estimates for TNBC patients treated with adjuvant/neoadjuvant chemotherapy (22,23). Increased TIL levels have been observed to be positively correlated with prolonged survival and increased pathological complete response rates (24)(25)(26). Because of the uneven distribution of TILs within the tumor, TIL levels obtained by biopsy in a specific part of the tumor may not reflect the entire tumor.…”
Section: Discussionmentioning
confidence: 99%
“…CD8+T cell played a direct and clear role on tumor cell (Giese, Hind & Huttenlocher, 2019;Okada et al, 2020;Taya et al, 2020). Previous studies showed that CD8+T cell infiltration improved a survival benefit of the patient with advanced cancer (Vihervuori et al, 2019). While activated, CD8+T cell induced tumor cell to express some factor to recruit macrophage, which weakened the efficacy of PDCD1 immunotherapy (Neubert et al, 2018).…”
Section: Infiltration Levelmentioning
confidence: 99%
“…The prognostic and predictive value of tumor-in ltrating lymphocytes (TILs) in breast cancer has been extensively studied in recent years, especially in triple negative and human epidermal growth factor receptor 2-enriched (HER2+) subtypes (1)(2)(3). High TIL levels, which seem to re ect favorable host antitumor immune responses, have been associated with improved clinical outcomes, increased rates of pathological complete response (pCR) to neoadjuvant therapy, and greater bene t from adjuvant therapy in triple negative breast cancers (TNBC) and HER2 + breast cancers (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to overall TIL levels, speci c immune cells have also been associated with survival and therapeutic responses. In particular, extensive tumor-in ltrating cytotoxic CD8 positive (CD8+) Tcells were strongly associated with patients' favorable survival and increased rates of pCR in response to neoadjuvant therapy (3,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%